Physiological features of skilled swimmers who specialize in crawle mode on the chest - Близнюк [Yuriy Bliznyuk] Юрій Володимирович; Ярёменко [T. Yaremenko] Т. В. (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> To the article the scores of research of 34th masters of sport are driven on swimming from the different cities of Ukraine, participants of national championship 2012 year on distances by free style. A research purpose consisted in determination of psikhofiziologichal model of swimming from the different cities of high qualification depending on his controlled from distance specialization. Distinctions are shown between sprinters, stayers and swimmers, specialized on midranges in such indexes, as: force of the nervous system in relation to excitation, maximal frequency of motions, latent time of reaction on the voice irritant of different power. <!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>